LIH KODE DALAM TAYANGAN LAPOR PAK PADA CHANNEL YOUTUBE TRANS7 LIFESTYLE - Nurdianti, Astri; Rosalina, Sinta (Universitas Hamzanwadi, 2022)
This study aims to explain the form of code switching and code switching contained in Lapor Pak broadcasts on the Trans7 Lifestyle Youtube Channel. The research approach a qualitative descriptive in the form of a description of the data obtained in the analysis. The data used is through the form of speech, sentences and paragraphs. Then the method used is a qualitative method. The data source for this research is the Youtube Lapor Pak program entitled Secret Mission to America which was published on December 14, 2021 with a duration of 48:07 minutes. The data collection technique used by the author in this study is through the listening technique and the note-taking techniques. The type of instrument used is in the form of non-participant observation, namely the author observes YouTube videos from start to finish. The results obtained in this study are the forms of code switching and the role of code switching contained in the Lapor Pak show on the Trans7 Lifestyle Youtube Channel. The forms of code switching obtained include; internal code switching from Indonesian to Javanese, then from Javanese to Indonesian. Then the external code switching switches from Indonesian to English and from English to Indonesian. While the role of code switching is as humor through the theory of Incongruity, Superiority, and Liberation theory.Keywords: Forms of code switching, Role of code switching, and Youtube.